Dynamics of vegetation in Karun watershed within Khuzestan province in relation with Temperature factors and precipitation - Saman alimoradi; Asadollah : khoorani; Yahya esmaeilpoor (تحقیقات کاربردی علوم جغرافیایی)
The aim of this study is to retrieve land surface temperature (LST), air temperature (AT) and precipitation and to study their relationship with vegetation in rang lands of Karun watershed of Khuzestan province. For this purpose, land surface temperature (LST) and NDVI was drived from NOAA-AVHRR for maximum amount of greenness (April) for a period of 27 years. In order to extract LST, Price algorithm was used. Also air temperature and precipitation were interpolated for selected weather stations using IDW method. Spatial correlation outcomes (on 0.05) between NDVI with LST and air temperature show a reversed relation. This spatial relation is stronger for LST, so that this coefficient is often upper than 0.6, while seldom is 0.4 for air temperature and precipitation. Spatial regression models show that 62 percent of NDVI changes is determined by LST (R2=0.62) and air temperature and precipitation determine very limited amount of NDVI dynamics.